2006
DOI: 10.1200/jco.2005.03.2573
|View full text |Cite|
|
Sign up to set email alerts
|

Radiotherapy As Primary Treatment for Stage IE and IIE Nasal Natural Killer/T-Cell Lymphoma

Abstract: RT as primary therapy resulted in good outcome in early-stage disease, and the addition of CT to RT was not accompanied by an improvement in survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
314
3
3

Year Published

2007
2007
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 316 publications
(336 citation statements)
references
References 59 publications
(47 reference statements)
15
314
3
3
Order By: Relevance
“…CHOP is regarded as the standard chemotherapy regimen for aggressive NHL, however, its effect in patients with extranodal NK/T-cell lymphoma, nasal type, is usually inferior. In the present study, a CR rate of 33% was achieved, which is consistent with previous literatures [8,18]; 35% of patients had PD during chemotherapy, suggesting primary drug-resistance may exist in some patients. P-gp, encoded by mdr-1 gene, has been extensively studied in various types of malignancies.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…CHOP is regarded as the standard chemotherapy regimen for aggressive NHL, however, its effect in patients with extranodal NK/T-cell lymphoma, nasal type, is usually inferior. In the present study, a CR rate of 33% was achieved, which is consistent with previous literatures [8,18]; 35% of patients had PD during chemotherapy, suggesting primary drug-resistance may exist in some patients. P-gp, encoded by mdr-1 gene, has been extensively studied in various types of malignancies.…”
Section: Discussionsupporting
confidence: 93%
“…Patients with later stage are usually less likely to achieve CR. Moreover, for patients with limited stage, Stage II was proved to be an adverse prognostic factor by multivariate analysis in a retrospective study mentioned earlier [8].…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Although improved survival with combined modality therapy was observed in our previous study of early stage NK/T-cell lymphoma of Waldeyer's ring, 26 no study so far has shown significant benefit of adding chemotherapy to radiotherapy in early stage nasal NK/T-cell lymphoma or early stage NK/T-cell lymphoma of the upper aerodigestive tract. 3,14,15,[20][21][22]33,34 Although the regimens and number of chemotherapy cycles administered varied somewhat, most (85%) of our patients received 4 cycles of standard CHOP or CHOPlike regimens. With high LRC after radiotherapy, no survival benefit of additional chemotherapy was observed in these patients with early stage nasal NK/T-cell lymphoma.…”
Section: Discussionmentioning
confidence: 98%
“…3,26 A dose of 50 to 56 grays (Gy) was given to the primary tumor, and 15 patients received a boost of 5 to 10 Gy to residual disease. Patients were treated with 1.8 to 2.0 Gy daily, 5Â a week.…”
Section: Treatmentmentioning
confidence: 99%